CAPITAL MARKET COMPANIES IN THE UAE: DETERMINANTS AND FACTORS AFFECTING THE PERFORMANCE OF LISTED UAE COMPANIES - Tariq Tawfeeq Yousif Alabdullah (Transpublika Publisher, 2023)
This research examines the influence of international ownership, national ownership, and CEO duality on organizational performance within listed organizations on the Dubai Financial Market (DFM). A multiple regression analysis was employed to assess the effects of international ownership, national ownership, and CEO duality on organizational performance. The study focused on 60 organizations during the fiscal year 2020. Through regression analysis of the collected data, the results indicate that national ownership has an insignificant yet positive impact on organizational performance. Furthermore, the findings demonstrate that international ownership significantly and positively affects organizational performance. Additionally, the analysis reveals that non-CEO duality positively correlates with organizational performance. The practical implications of this study are reflected in its findings, which underscore the importance of the independent variables within the context of investment possibilities—serving as proxies in our study. These findings enhance the understanding of the value of robust corporate governance elements, not solely for directly enhancing organizational performance, but also for amplifying their influence on external factors. Such insights can prove valuable to various stakeholders, including policymakers, regulators, and other interested parties, in their review of procedures in the UAE, particularly following the implementation of corporate governance laws. This study contributes to the existing literature by highlighting the roles played by international ownership, national ownership, and CEO non-duality in enhancing organizational performance.